Credit Risk Determinants in European Banking: Evidence from Albania, Italy, Spain and Turkey (1998-2016) - Gourgoura, Esida (School of Economics, 2022)
Credit risk has always been a major risk in banking given that financial crises are usually associated by an increase on loan defaults. The 2008 global financial crisis revealed the fragility of banking systems and highlighted the importance of identifying the determinants of credit risk, in order to prevent banking systems from collapse and as such to maintain the stability of the whole financial system. In the aftermath of the 2008 crash, Europe was faced with another crisis, namely, the Eurozone debt crisis that considerably affected several developed countries especially those that are characterized as peripheral European countries. In parallel with the increased risk of default on their debts, these countries also faced tremendous problems in their banking sectors as the quality of loans granted by their banks further deteriorated, enhancing the argument that credit risk is an issue of core interest to financial stability. Moreover, the high dominance of some peripheral countries‘ banks in the banking sectors of less developed European economies (i.e. Albania) suggests that specific events in these countries might have a spillover effect. Based on quarterly data over the period 1998-2016, this thesis provides empirical evidence on the link between credit risk and a range of explanatory variables for four European countries, namely, Albania, Italy, Spain and Turkey. Motivated by the weak economic conditions and the increased bank credit risk in Italy and Spain in the aftermath of the sovereign debt crisis as well as by the significant presence of Italian and Spanish banks in the banking systems of Albania and Turkey respectively, the contribution of the thesis is fourfold: First, a thorough credit risk investigation is provided for each focal country, based on unique features, exclusively related to them (such as the Italian and the Spanish debt crisis spreads that proxy the sovereign debt crisis risks in Italy and Spain respectively). Secondly, a spillover effect of the sovereign debt crisis in Albania and Turkey is investigated since it is believed that shocks may be easily transmitted through bank and trade channels even to economies that are not directly exposed to the crisis. To the author‘s knowledge, this is the first time that such a spillover effect is investigated in the relevant literature. Thirdly, a wider timeframe is investigated, compared to that analyzed in the previous studies, which captures the booming period (1998-2007), the global financial crisis (2008- 2009) and the ensuing European sovereign debt crisis (2010-2012) where Italy and Spain were deeply involved as well as the aftermath of the two crises (2013-2016). Lastly, the empirical research is based on the ARDL approach to cointegration, which is rarely applied in the existing literature on credit risk and holds certain advantages against other econometric techniques. Besides, the methodological approach is complemented by robustness checks through the use of other approaches such as the VECM framework and the impulse response analysis. Findings suggest that macroeconomic, bank-specific, and financial markets‘ variables affect credit risk in the Albanian, Italian, Spanish and Turkish banking systems. The positive effects of the Italian and the Spanish sovereign debts on credit risk uncover the important link that exists between banking and the sovereign debt crisis. Moreover, findings suggest a contagious effect of the Italian debt crisis in Albania, given that the Italian debt crisis spread has a significantly positive effect on the Albanian credit risk. A similar spillover effect (of the Spanish debt crisis spread) in the Turkish credit risk does not appear to be significant, indicating that in contrast to Albania, the Turkish banking system is more domestically oriented. The findings‘ diversity among the focal countries emphasizes the role of country-specific features in determining credit risk and the importance of country case - studies to credit risk modeling; individualized results can be thoroughly interpreted by policy makers in each country, and thus, may be effectively used to regulate accordingly.